DEVELOPMENT OF A METHODOLOGY FOR DIGITIZING THE INVENTORY OF TANGIBLE TECHNICAL DEVICES IN THE DIGITAL ECONOMY - Izzatilla Pulatov Qudratillayevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article proposes a new IRC (Integrated Concept of Material Resources) model for managing material and technical resources of educational organizations along the entire life cycle (reception → inventory → dispatch → repair → write-off). The model is developed on the basis of tables with deep integration with blockchain technology, providing real-time planning and management of each movement of resources. According to the pilot organization conducted by the IRC in the Tashkent organization, there is no loss and destruction model. This is the first practical experience of blockchain and tabular integration in budget resource management.